2015
DOI: 10.1038/ejhg.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the 3’untranslated region of APP as a genetic determinant of cerebral amyloid angiopathy

Abstract: Aβ-related cerebral amyloid angiopathy (CAA) is a major cause of primary non-traumatic brain hemorrhage. In families with an early onset of the disease, CAA can be due to amyloid precursor protein (APP) pathogenic variants or duplications. APP duplications lead to a~1.5-fold increased APP expression, resulting in Aβ overproduction and deposition in the walls of leptomeningeal vessels. We hypothesized that rare variants in the 3'untranslated region (UTR) of APP might lead to APP overexpression in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…16,17 Variants in these elements, particularly those effecting 5ʹ and 3ʹ UTR mRNA secondary structures have been linked to disease. [17][18][19][20] Taken together, our combined genetic, experimental and modelling evidence suggests that NC_000023.10:g.69665044dupG variant alters SAP102 protein abundance, which is the most plausible cause of moderate non-syndromic ID this family.…”
Section: Discussionmentioning
confidence: 78%
“…16,17 Variants in these elements, particularly those effecting 5ʹ and 3ʹ UTR mRNA secondary structures have been linked to disease. [17][18][19][20] Taken together, our combined genetic, experimental and modelling evidence suggests that NC_000023.10:g.69665044dupG variant alters SAP102 protein abundance, which is the most plausible cause of moderate non-syndromic ID this family.…”
Section: Discussionmentioning
confidence: 78%
“…Only one study has demonstrated the role of miR-770-5p, and bioinformatic analysis revealed that it likely contributed to apoptosis and hippocampal signaling pathways and was involved in the molecular mechanisms underlying temporal lobe epilepsy memory disorders 28 . Like miR-770-5p, recent study suggested that miR-892b was correlated with retinopathy and neurological diseases 29 30 . These results suggest that this miRNA is a potential contributor to diabetic neuropathy and retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of non‐coding regions of the App gene precludes the analysis of splicing of APP mRNA and transcriptional regulation involving these gene regions (Nicolas et al , 2016). …”
Section: Limitations Of First‐generation Mouse Modelsmentioning
confidence: 99%